2019
DOI: 10.18203/2394-6040.ijcmph20194490
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, sociability and depression in old age home elderly

Abstract: Background: Increasing elderly population became a big concern to health professionals. Loneliness, lack of socialization and depression is quite frequently reported in elderly population. Lack of evidence on impact of socialization and loneliness on depression necessitate this survey. The current work focused on level of socialization, loneliness and depression among elderly residing in old age homes.Methods: The cross-sectional survey includes 100 purposively selected elderly from selected old age homes, Utt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…The data was screened and the findings were presented in the order of objectives of the research. [18] , found that loneliness and sociability had a significant relationship, however their correlation was weak, at .195, similar to that found in the current study. A different sample, might give more significant results, however, the correlation might still remain weak.…”
Section: Resultssupporting
confidence: 87%
“…The data was screened and the findings were presented in the order of objectives of the research. [18] , found that loneliness and sociability had a significant relationship, however their correlation was weak, at .195, similar to that found in the current study. A different sample, might give more significant results, however, the correlation might still remain weak.…”
Section: Resultssupporting
confidence: 87%
“…Both phenomenon have been declared a global epidemic in older adults in 2017 ( Lambrini, 2016 ). Between one third and half of the older adults across the world and in India have reported varying degrees of loneliness and social isolation prior to the onset of the COVID-19 pandemic in December 2019 ( Singh and Misra, 2009 ; Panwar et al., 2019 ).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…It beneficial for students personalized Learning. In the research of Panwar, Kumar, and Belsiyal (2019) it was found that e-learning may be effective in developing cognitive abilities of pupil teachers. The result found the students of e-learning program had higher achievement levels than their counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to motivate, develop confidence and self-esteem, overcome many barriers that learners encounters, personalize the learning experience widen access, and improve the learning experience while also helping people develop their ICT skills. In the research of Panwar, Kumar, and Belsiyal (2019), e-learning may be effective in developing the cognitive abilities of pupil teachers. The result found the students of the e-learning program had higher achievement levels than their counterparts.…”
Section: Introductionmentioning
confidence: 99%